PENGARUH PEMANFAATAN MEDIA DIGITAL TERHADAP CIVIC LITERACY PESERTA DIDIK DI SMAN 2 KOTABUMI - Ratna Wulandari; Muhammad Mona Adha; Nurhayati Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of digital media utilization on improving students' civic literacy at SMAN 2 Kotabumi. The study was motivated by the importance of utilizing digital media in the learning process to support the enhancement of students' civic literacy in Pancasila Education. The use of digital media is expected to facilitate a more effective, interactive, and innovative learning process. This research employed a descriptive method with a quantitative approach. The subjects of this study were students of SMAN 2 Kotabumi, with a total sample of 60 respondents. Data were collected using a questionnaire as the research instrument. Data analysis was conducted using SPSS software to examine the effect of digital media utilization on students' civic literacy. The results indicate that digital media utilization has a significant positive effect on improving students' civic literacy at SMAN 2 Kotabumi. The utilization of digital media, including digital media-based learning planning, selection of digital learning media, implementation of digital media in the learning process, and evaluation of digital media use, contributed positively to the enhancement of students' civic literacy. Students' civic literacy, which encompasses civic knowledge, civic skills, and civic attitudes and participation, demonstrated positive development through learning activities supported by digital technology. Therefore, the utilization of digital media not only serves as a supporting tool in the learning process but also plays a significant role in enhancing students' civic literacy at SMAN 2 Kotabumi.